2019
DOI: 10.1542/peds.2019-0347
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity and Health Care Use

Abstract: BACKGROUND AND OBJECTIVES: Fifteen percent of US children live in households with inadequate food. Children who are food insecure often experience worse physical, emotional, and developmental health outcomes. Authors of previous studies have not examined the quality and cost implications of food insecurity in children. METHODS: This is a retrospective study of 7959 nationally representative US children (aged 1-17 years) in the 2016 Medical Expenditure Panel Survey. Households with food insecurity were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
53
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 25 publications
(47 reference statements)
2
53
1
Order By: Relevance
“…In parallel, given the aforementioned association between multimorbidity and food insecurity, US-based research has suggested that food-insecure individuals tend to make extended use of the health care services, irrespectively of their age [6,12]. Due to the differences in the two healthcare systems, this finding was not verified in the present sample.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…In parallel, given the aforementioned association between multimorbidity and food insecurity, US-based research has suggested that food-insecure individuals tend to make extended use of the health care services, irrespectively of their age [6,12]. Due to the differences in the two healthcare systems, this finding was not verified in the present sample.…”
Section: Discussioncontrasting
confidence: 54%
“…Although a lack of relevant pre-recession data is apparent, proxy measures as food banks and food assistance indicate that the number of food-insecure older adults surged as an epiphenomenon of the financial crisis and the austerity measures taken by the government [4,35]. In the US, the prevalence of adult food insecurity inside the health care setting has been reported to range between 13.2-19.1% [12,13,36]; however, one possible explanation for the observed among-country difference lays to the fact that in Greece, health care provision is provided to all for free, whereas in the US only insured individuals make use of the health care resources. In parallel, even in the US, research in the private health care setting has revealed a much lower prevalence of food insecurity compared with the public sector [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FI is often transient, with children and families moving in and out of FI over time due to changes in family circumstances or seasonal fluctuations in food availability due, for example, to changes in household expenses, and availability of school meals [11][12][13]. However, to date, the majority of studies evaluating programs that screen and address FI in clinical care settings have been cross-sectional [3,14,15]. Few studies have demonstrated FI patterns longitudinally among a cohort of pediatric participants in a clinical setting [16].…”
Section: Introductionmentioning
confidence: 99%
“…Poverty and associated social determinants of health, such as food insecurity and housing instability, can adversely affect children' s health and development. [1][2][3][4][5] In 2016, the American Academy of Pediatrics (AAP) released a policy statement encouraging community pediatricians to screen for unmet social needs in order to identify families in need and connect them to community resources. 6 However, implementing successful screening and referral programs has been challenging.…”
mentioning
confidence: 99%